Continuing the Journey to the West: the American-led Chinese story and creative transformation - Tian Wang; Farideh Alizadeh; Rosdeen bin Suboh (Cogent Arts & Humanities)
Hollywood’s The Forbidden Kingdom (2008) and Netflix’s The Monkey King (2023) exemplify what can transpire when the Chinese canonical work Journey to the West continues its journey westward to the United States of America rather than stopping at the story’s original destination, India. This study conducted a comparative analysis of the novel and these two films based on the creative transformation theory to explore the transcultural film adaptation in the United States and offer new ideas for the creative transformation of traditional Chinese culture. Findings revealed that the diversity of the novel’s content provides the opportunity for multiple interpretations by individuals from various cultural backgrounds, thereby creating the potential for transcultural adaptation. Each American adaptation can be viewed as a transcultural dialogue between contemporary American and traditional Chinese culture. During the dialogue, this novel and the traditional Chinese culture it contains and reflects show a world-oriented creative transformation that encompasses plenty of universal values. Although this study cannot encapsulate the panoply of transcultural adaptation activities for Journey to the West, it may serve as an entry point to depict a clear picture of the novel’s transcultural film adaptations in the United States.